Pattern of muscle contraction in car pedal control - Nor Kamaliana Khamis,; Baba Md Deros,; Mohd Zaki Nuawia,; Schramm, Dieter (Penerbit Universiti Kebangsaan Malaysia, 2018)
Driver’s discomfort has gained a lot of attention, especially among interested parties. There are many interacting factors involving both the driver and the interior components of the car that contribute to discomfort while driving. In this study, an investigation was carried out on the contraction of the lower leg muscle among drivers when operating the accelerator pedal. The main objective of this study was to determine the pattern of muscle contraction when operating the accelerator pedal with regard to three different actions; pressing, half-pressing and releasing. Eleven participants were involved in this investigation into the muscle pattern, whereby surface electromyography (SEMG) was used to measure the activity of the lower leg muscle, known as the tibialis anterior (TA). The data collection procedure on the selected muscle was in accordance with the SEMG recommendations for the Non-Invasive Assessment of Muscles. Based on the results, the TA depicted that the highest muscle contraction occurred during the releasing action. In addition, there were significant differences between each action in the T-test analysis with p < 0.05. It can be concluded that the TA muscle works differently based on the car pedal actions.